The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1177/001857870203701011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Impact on Pneumococcal Vaccination Rates through Incorporation of Immunization Assessment into Critical Pathways in an Acute Care Setting

Abstract: Despite the availability of effective prevention and treatment measures, pneumococcal infection continues to be a significant source of morbidity and mortality. This study evaluated the impact of incorporating the assessment of pneumococcal vaccination status into selected critical pathways of at-risk patients. In a prospective, nonblinded, parallel-group trial, adult inpatients on four critical pathways were randomized into intervention or control groups. Nursing personnel screened all patients for previous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The results of this study make pharmacy technician follow-up one of the most successful interventions for improving inpatient vaccination rates to date. 8,[22][23][24][25][26][27] Due to the relatively low cost of pharmacy technicians in comparison with nursing and pharmacist salaries, the relative cost-effectiveness of this intervention could merit additional investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study make pharmacy technician follow-up one of the most successful interventions for improving inpatient vaccination rates to date. 8,[22][23][24][25][26][27] Due to the relatively low cost of pharmacy technicians in comparison with nursing and pharmacist salaries, the relative cost-effectiveness of this intervention could merit additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…13-21 Pharmacists have previously demonstrated their value in improving vaccination rates through targeted follow-up reminders to physicians and pharmacist-managed SOP’s. 8,22-26 An additional method utilized by pharmacy departments has been development of a collaborative drug therapy management (CDTM) agreement which authorized pharmacists to write influenza and pneumococcal orders for eligible patients which similarly resulted in improved vaccination rates. 27 These pharmacy-driven initiatives have led to improved inpatient vaccination rates but have been resource-intensive consisting of manual chart review, patient interviews, and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…25 Pharmacists are skilled at medication counseling and have previously been demonstrated to be especially effective at screening and identifying candidates for vaccination and as immunization educators. 24,26 In fact, 30 states currently allow pharmacists to administer immunizations, although this is not currently permitted by New York state law. 25 Our program was sustainable by assigning the screening, consent, and standing orders activation responsibilities to the already existing pharmacy staff and was thus cost-neutral.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] A variety of approaches to promote inpatient pneumococcal vaccination have been implemented, including computerized reminders to physicians at the time of patient discharge, stamped notes on hospital charts, vaccination prompts embedded in pneumonia clinical pathways, and standing orders protocols. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Study methodologies and interventions and reported results vary. 11 None of the most successful immunization programs described to date has depended on active physician participation.…”
mentioning
confidence: 99%
“…When eligible patients were identified in the intervention group, the pharmacist would contact their physician for authorization to vaccinate. 22 This approach led to a significant increase in vaccination rates in the intervention group (n = 107) versus the control group (n = 124) (73.8% versus 46.8%). While effective, this process was both timeconsuming and cumbersome, with the rate-limiting step being the need to contact patients' physicians.…”
Section: Introductionmentioning
confidence: 99%